Thermal energy generation in the earth - F. J. Mayer; J. R. Reitz (Nonlinear Processes in Geophysics, 2014)
We show that a recently introduced class of electromagnetic composite particles can explain some discrepancies in observations involving heat and helium released from the earth. Energy release during the formation of the composites and subsequent nuclear reactions involving the composites are described that can quantitatively account for the discrepancies and are expected to have implications in other areas of geophysics – for example, a new picture of heat production and volcanism in the earth is presented.